#TITLE_ALTERNATIVE# - ODE MUHAMMAD RIZAL (NIM 24206004); Pembimbing: Prof. Dr. Ir. Agus Salim Ridwan, M.Sc., dan Ir. Da, LA
High speed exit taxiway is one of facility from runway. Because the important function in determination of runway usage time hence location of high speed exit taxiway selected in such a manner so that runway plane remained time can be shortened.<p.This research observes process of plane landing start from runway threshold, touchdown till plane reached speed in high speed exit taxiway. By using normal curve as probability distribution of high speed exit taxiway location ideal to every plane category got location of high speed exit taxiway giving addition of usage time smallest runway. The research was conducted in north runway of Soekarno-Hatta Airport showed that for landing from 07L direction only needed one addition of high speed exit taxiway at distance 1830 metre from threshold. This addition will degrade runway usage time every C category plane from 35 second become 5 second, so that potential to improve capacities up to 6 movement per hour. For plane that was landing from 25R direction can be done addition of high speed exit taxiway at distance 2350 metre from threshold 25R. This addition was meant to degrade addition of runway usage time of runway every D category plane from 25 second become 4 second, so that potential to improve capacities up to 4 movement per hour.